Aplikasi Dan Website Sistem Informasi Pendataan Kerja Praktek Dan Skripsi Mahasiswa Jurusan Teknik Elektro Fakultas Teknik Universitas Riau - Budi Prasetyo; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Currently, the Department of Electrical Engineering, Universitas Riau is still using paper documents for internship and final project registration. Thus, the archives that have been stored in a place will be potentially be lost. This is due to human error in management or other reasons. All paper documents need a lot of time, resulting long response to be completed. To overcome this problem, a revolution of online information system is needed in order to save time and provide fast response. The designed online information system is successfully performed using Basic Language and Ms Access as a database for standalone, and MySQL database for website application.Keywords: Internship, Thesis, Database, Website.